Miejsce teorii porowatości biota w mechanice ośrodków ciągłych - Solecki, R. (Engineering Transactions, 1968)
The paper contains a critical comparison of the Biot consolidation theory with more modern theories, in particular with Green’s theory. The author demonstrates the limited range applicability of the Biot theory, indicating that it neglects the diffusion resistance.